Financial Inclusion and Macroeconomic Stability in Eight Southeast Asian Economies - Gitaharie, Beta Yulianita (Universitas Negeri Semarang, 2023)
More than six in ten people in developing countries in Southeast Asia are unbanked. It may be for this reason that ASEAN prioritizes financial inclusion and financial stability. Financial inclusion aims to enlarge the proportion of the population to access and use financial services. The objectives of this study are to construct financial inclusion index and to investigate the relationship between the constructed index and the macroeconomic stability variables—financial stability, inflation volatility, and output volatility– in eight Southeast Asian countries for the 2008-2020 period. The three-dimension—access and availability, usage, and technology/infrastructure– financial inclusion index is constructed using a double principal component method. The result shows that Indonesia (0.55) and Lao (0.53) are the two countries with the highest average index for the period. Employing the panel seemingly unrelated regression, the study finds that financial inclusion has a positive effect on financial stability; and a negative effect on inflation and output volatility. The finding supports the ASEAN authority to continuously expand financial inclusion as it contributes to increasing financial stability, reducing inflation and output volatility, hence, the macroeconomic stability.